Studies on the formation of specific nervous connections - Pilgrim, A (1981)
This thesis is concerned with the way in which precise patterned connections are formed between groups of neurones and their targets. Two theories are discussed: the chemospecificity hypothesis, according to which these connections are formed by the matching of detailed labels carried by the neurones and their targets; and the morphogenetic model in which the orderly and passive growth of nerve fibres determines the pattern of synapses formed. Two pathways previously thought to be disorderly, peripheral nerves and the mouse optic nerve, were studied and their fibres were found to be actually arranged in an ordered fashion. The goldfish retinotectal pathway was also studied, and the apparently complex reorganization of the fibre array needed to generate the observed projection was found to be explicable by the passive guidance of optic axons over the optic cup and stalk. Regeneration of optic fibres within the goldfish retinotectal system was investigated. It was found that distortions of the normal fibre ordering could be corrected within the pathway and also at the tecturn. Some means of active fibre guidance was therefore indicated, but this was found incapable of correcting certain instances of gross disordering. In some experiments fibres were forced to project to the ipsilateral tectum in the absence, presence, or during the regeneration of, the normal contralateral projection. In the tecta of two-eyed fish interactions between the two fibre populations were detected, leading in some fish to the incomplete segregation of the two groups into patches. In conclusion the development of specific neural connections was considered to be more than the consequence of the passive maintenance of fibre order within neural pathways. Active self-ordering of fibres on the basis of their positions of origin could explain additional phenomena present in regeneration, and would be an economical way of correcting mistakes made in development.